(untitled) (Scientific journal of the Fergana State University, 2025)
Zinc oxide (ZnO) nanoparticles are of great interest in materials science due to their high photocatalytic activity, non-toxic nature, and versatile applications. In this study, ZnO nanoparticles were synthesized on the surface of a locally sourced PPE-1 polymer anionite using three different methods: precipitation, sol-gel, and green synthesis. The synthesis processes were focused on ensuring the integration of ZnO with the polymer, which allowed the creation of nanocomposites with novel functional properties. The resulting ZnO/PPE-1 nanocomposites were characterized using infrared (IR) and Raman spectroscopy. In the IR spectra, frequencies of 423–525 cm⁻¹ characteristic of Zn-O bonds were detected, while Raman analysis confirmed the interaction between the amine groups in the polymer and ZnO. These results indicated the successful formation of ZnO nanoparticles on the polymer surface. The study highlighted the potential of ZnO/PPE-1 nanocomposite for photocatalytic purification, particularly for photocatalytic degradation of organic pollutants. The practical significance of the work lies in the development of effective materials for water purification technologies.